Differences in the epidemiology between paediatric and adult invasive Streptococcus pyogenes infections. - Zachariadou, L; Stathi, A; Tassios, P T; Pangalis, A; Legakis, N J; J Papaparaskevas (Epidemiol Infect, 2014)
In order to investigate for possible differences between paediatric and adult invasive Streptococcus pyogenes (iGAS) infections, a total of 142 cases were identified in 17 Greek hospitals during 2003-2007, of which 96 were children and 46 adults. Bacteraemia, soft tissue infections, streptococcal toxic shock syndrome (STSS), and necrotizing fasciitis were the main clinical presentations (67·6%, 45·1%, 13·4%, and 12·0% of cases, respectively). Bacteraemia and lymphadenitis were significantly more frequent in children (P=0·019 and 0·021, respectively), whereas STSS was more frequent in adults (P=0·017). The main predisposing factors in children were varicella and streptococcal pharyngotonsillitis (25% and 19·8%, respectively), as opposed to malignancy, intravenous drug abuse and diabetes mellitus in adults (19·6%, 15·2% and 10·9%, respectively). Of the two dominant emm-types, 1 and 12 (28·2% and 8·5%, respectively), the proportion of emm-type 12 remained stable during the study period, whereas emm-type 1 rates fluctuated considerably. Strains of emm-type 1 from children were associated with erythromycin susceptibility, STSS and intensive-care-unit admission, whereas emm-type 12 isolates from adults were associated with erythromycin and clindamycin resistance. Finally, specific emm-types were detected exclusively in adults or in children. In conclusion, several clinical and epidemiological differences were detected, that could prove useful in designing age-focused strategies for prevention and treatment of iGAS infections.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Antigens, Bacterial; Bacterial Outer Membrane Proteins; Carrier Proteins; Child; Child, Preschool; Drug Resistance, Multiple, Bacterial; Female; Greece; Humans; Infant; Male; Middle Aged; Prospective Studies; Questionnaires; Risk Factors; Streptococcal Infections; Streptococcus pyogenes